2022
DOI: 10.48550/arxiv.2202.07163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snowmass White Paper: Bootstrapping String Theory

Rajesh Gopakumar,
Eric Perlmutter,
Silviu S. Pufu
et al.

Abstract: We discuss progress and prospects in the application of bootstrap methods to string theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 262 publications
(325 reference statements)
0
47
0
1
Order By: Relevance
“…Finally, let us remark that the D-instanton amplitudes of the sort computed in this paper may provide useful input for the program of bootstrapping the non-perturbative string Smatrix [50,51].…”
Section: Discussionmentioning
confidence: 90%
“…Finally, let us remark that the D-instanton amplitudes of the sort computed in this paper may provide useful input for the program of bootstrapping the non-perturbative string Smatrix [50,51].…”
Section: Discussionmentioning
confidence: 90%
“…Following the numerical S-matrix bootstrap program, bounds on the gravitational EFTs have been considered in [99] where it is shown that the constraints on the allowed Wilson coefficient of the leading non-trivial corrections to D = 10 maximal supergravity fit well with the range of allowed values expected in string theory (see the Snowmass white paper on bootstrapping string theory [100]).…”
Section: Unitarity and Causality Bounds For Gravitational Eftsmentioning
confidence: 99%
“…In this section, we focus on progress towards the quantization of Type IIB strings on AdS backgrounds, and the interplay between conformal correlators in strongly coupled N = 4 SYM and SL(2, Z) duality. A separate White Paper is dedicated to progress [201] on establishing the map between conformal correlators and string perturbation theory.…”
Section: Gauge/gravity Dualitymentioning
confidence: 99%